1987
DOI: 10.1007/bf01907020
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and Ca++ activation of the cardiac contractile system: hereditary cardiomyopathy in hamsters (BIO 14.6), isoprenaline overload and the effect of APP 201-533

Abstract: In the present paper, two experimental models of heart failure, namely hereditary cardiomyopathy in hamsters (BIO 14.6) and cardiac insufficiency due to mild (0.06 microM) isoprenaline overload of rabbit isolated perfused hearts, were compared in terms of resulting alterations at the level of the functionally isolated contractile system of detergent/glycerol treated skinned cardiac fibres. As the main features of Ca activation of tension in these models, the following were found: 1. Within the same species (RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The sensitivity to ISO depends on age, with young animals being more resistant (Faltova et al 1983a;Kojima 1983;Herzig et al 1987), sex (Faltova et aI. 1980) and body mass (Faltova et aI.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity to ISO depends on age, with young animals being more resistant (Faltova et al 1983a;Kojima 1983;Herzig et al 1987), sex (Faltova et aI. 1980) and body mass (Faltova et aI.…”
Section: Discussionmentioning
confidence: 99%
“…Thin fibres with a diameter of 0.1-0.3 mm and a length of 4-6 mm were attached to a mechanical equipment designed for isometric force measurement as described by Herzig et al [18], using the isometric contraction sensor AE 801 (Senso Nor a.a., Horten, Norway). Contractions were elicited by incubation of the fibres in solutions with various EGTA-buffered Ca 2+ concentrations, containing Na 2 ATP, while phosphoenolpyruvate and pyruvate kinase served as an ATP regenerating system.…”
Section: Measurement Of the Contractility And The Atpase Activity Of mentioning
confidence: 99%
“…Increasing cardiac contractility without increasing cytosolic calcium represents an attractive mechanism for a positive inotropic agent, since increasing intracellular calcium in the failing heart may precipitate calcium overload and cell death [54,55]. In a recent report, Weishaar et al [56] showed that chronic administration of digitalis to cardiomyopathic hamsters exacerbated the rise in myocardial calcium normally observed in these animals and also increased the incidence of myocardial necrosis.…”
Section: Calcium Sensitizersmentioning
confidence: 99%
“…These other agents include pimobendan [54], MCI-154 [57], BM 14.578 [58], APP 201-533 [55], and DPI-201-106 [59]. Most of these agents, however, have been shown to exert other actions that could increase cardiac contractility, including inhibition of phosphodiesterase (pimobendan and sulmazole), inhibition of Na, KATPase (sulmazole), and stimulation of the sodium fast channel (DPI-201-106) [60][61][62][63].…”
Section: Calcium Sensitizersmentioning
confidence: 99%